Physicochemical and Spectroscopic Elemental Analysis of Ground Water in Thickly Populated and Industrial Area of Quetta Valley Pakistan - Khan, Hayatullah; Kakar , Attiq-ur-Rehman; Khan, Samiullah; Khan , Naqeebullah; Ali , Irshad; Achakzai , Abdul Baqi (Al-Nahrain Journal of Science, 2019)
Quetta valley the capital of Balochistan Province, has faced twice the rush of immigrants i.e; Afghan refugees after Saur Revolution and people from interior Balochistan due to drought in Balochishan from the last two decades. Additionally a number of industries at various areas has been established. This abrupt increase in the population and discharge from the industries have affected the drinking water quality in the valley. To assess these affects, nine ground water samples taken from densely populated and industrial areas were analyzed for their physicochemical (taste, order, color, temperature, conductivity, turbidity, alkalinity, pH, total hardness and total dissolved salts) and concentrations of cations (Na, K, Fe, Mn, Co, Ni, Cu, Cd and Pb) by Flame Photometer and Atomic Absorption Spectrometer. The results obtained were compared with both Pakistan National Standards (PNS) for drinking water Quality (2010) and World Health Organization (WHO), standards for drinking water. All the results were in the limits of the standards except cobalt (0.095 – 0.12 mg/L) and cadmium (0.0348 – 0.041 mg/L) which were found to be in high concentrations that are attributed to the anthropogenic activates.